Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1007/bf01295726
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of villus and crypt cell functions in rat small intestine

Abstract: To evaluate the role of dietary polyamines in maturation of the rat small intestine, spermine was given orally twice daily to suckling pups from day 10 to day 14 postpartum at different doses: 0, 0.2, 0.5, 1, 2.5, and 5 mumol/dose. Compared to saline treated controls, spermine (5 mumol) produced significant increases in mucosal mass parameters (+12 to +57%, P < 0.05), induced prematurely an adult pattern of microvillous enzymes, and enhanced, respectively, by 19- and 3.5-fold (P < 0.01 vs controls) the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
2
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 29 publications
10
70
2
6
Order By: Relevance
“…2C). The observed increase in maltase SA in weaned piglets confirmed previous data obtained with rat pups under the same physiological conditions (Dufour et al 1988;Buts et al 1993;W ery & Dandrifosse, 1993). Compared to the fairly constant protein content observed in both parts of the gut at the two growth stages analysed, the Polyamines in pig gastrointestinal tract Exp.…”
Section: ------------------------------------------------------------supporting
confidence: 80%
See 2 more Smart Citations
“…2C). The observed increase in maltase SA in weaned piglets confirmed previous data obtained with rat pups under the same physiological conditions (Dufour et al 1988;Buts et al 1993;W ery & Dandrifosse, 1993). Compared to the fairly constant protein content observed in both parts of the gut at the two growth stages analysed, the Polyamines in pig gastrointestinal tract Exp.…”
Section: ------------------------------------------------------------supporting
confidence: 80%
“…Finally, it also seems logical that mechanisms ensuring a sustained cellular homeostasis should prevent an excessive accumulation of osmotically active polycations such as PAs in RBCs. Based on observations made earlier on rat pups (Dufour et al 1988;Dandrifosse et al 1992;Buts et al 1993;W ery & Dandrifosse, 1993;Dorhout et al 1997), one could expect that oral administration of SPM to suckling piglets would accelerate the maturation of the pig intestinal mucosa. Among other things, a stimulation of differentiation can be discerned S. Loret and others Exp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In suckling rats treated orally with spermine, the increase in the intestinal content of spermine in comparison with control rats is probably due to the intake, at the apical pole of the epithelial cells, of a higher quantity of this polyamine that is present in the gut lumen, rather than to a higher contribution via blood circulation, because intraperitoneal administration of spermine was without effect. Moreover, Dufour et al [36] and Buts et al [37] showed respectively either no modification or a decrease in the activity of the ornithine decarboxylase in suckling rats treated with spermine, indicating that the biosynthesis of spermine in enterocytes should not increase after the treatment of suckling rats with spermine.…”
Section: Discussionmentioning
confidence: 98%
“…En la Tabla 2 se muestra un breve resumen de los trabajos publicados en este campo. 13,33,[44][45][46][47][48][49][50] La elevada síntesis fetal de poliaminas durante la gestación, junto con las considerables y significativas variaciones de estas aminas durante los primeros días de vida en niños prematuros y nacidos a término, se han relacionado con su papel sobre el desarrollo, diferenciación y crecimiento celular en el organismo. 51 Además, la síntesis de poliaminas, especialmente de espermidina, aumenta progresivamente en la glándula mamaria durante los períodos de gestación y lactancia.…”
Section: Funcionesunclassified